Personal Branding Practice of Rural Influencers on TikTok (Douyin) in China - Lu,Yan (2025)
With the rapid diffusion of short video social media, a wave of rural influencers has emerged on China’s TikTok (Douyin), using short-form content to build personal brands and engage in sociocultural expression. Anchored in practice theory (Shove et al., 2012), this study adopts the “material–competence–meaning” triadic model to examine how these rural creators strategically construct personal brands under resource constraints (e.g., limited equipment, skills, and capital). Focusing on symbolic choices, adaptive tactics, and audience engagement, the study investigates branding practices in an under-resourced context. Employing a qualitative approach, the research draws on semi-structured and elicitation interviews with 11 rural TikTok influencers. Thematic analysis, supported by process auditing, reveals three main findings. First, in the initial stages of brand construction, rural creators often rely on localized cultural symbols to visually translate and construct brand identities. This process demonstrates a dynamic synergy among the elements of material, competence, and meaning. Notably, the sustainability of brand differentiation lies not in the uniqueness of initial symbols, but in the flexible and evolving meaning systems. Second, resource constraints are not barriers to innovation; instead, they serve as catalysts for differentiation, fostering creative bricolage and stylistic experimentation, and highlighting the generative nature of brand competence in practice. Third, rural creators enhance the social meaning of their brands through emotional engagement and community building with their audiences, gradually transforming their personal brands into tools for local service and cultural transmission, thereby enhancing their social legitimacy and cultural value. This study extends personal branding theory into resource-constrained, non-urban con-texts and underscores the cultural agency of marginalized creators on digital platforms.
Keywords: personal branding; TikTok; influencer; rural creator; social media; short video platform; self-brand